Analisis Determinan Kemiskinan Multidimensi Anak Di Pulau Papua Tahun 2021 - Rekha Novalina; Aisyah Fitri Yuniasih (Politeknik Statistika STIS, 2022)
One of the main focuses of every country in the world, including Indonesia, is alleviating poverty. Papua Island, which consists of the provinces of Papua and West Papua, has the highest percentage of poverty in recent years. Likewise, the highest level of child poverty (monetary and non-monetary approaches) is on the island of Papua. Based on BPS data (2021), poverty in Papua Island is more common in children aged less than 18 years. This study uses the MODA approach to determine the poverty status of children and multilevel binary logistic regression to analyze the determinants of child poverty. The results obtained that individual characteristics have a significant effect on child poverty, namely the age of the child. The household characteristics that influence are the gender and age of the head of the household (KRT), the number of household members (ART), the education of the head of the household (KRT), the type of area, the poverty status of the household, the status of the household receiving credit. The regional characteristic that influences child poverty is the Human Development Index (IPM).